Russian grand strategy rhetoric and reality - Charap, Samuel 1980-; Massicot, Dara; Priebe, Miranda; Demus, Alyssa; Reach, Clinton Bruce; Stalczynski, Mark; Han, Eugeniu; Davis, Lynn E. 1943- (RAND, 2021)
The study of a state's grand strategy can provide key insights into the direction of its foreign policy and its responses to national security challenges. Understanding Russia's grand strategy therefore can help U.S. decisionmakers both avoid strategic surprise by anticipating Moscow's actions and reactions and assess the depth and nature of potential conflicts between Russia and the United States. Because grand strategy is more than a collection of proclaimed foreign policy goals, a country's grand strategy must be understood through both a study of key documents and statements and a close empirical analysis of patterns of behavior. The authors of this report thus both describe Russia's declared grand strategy and test key elements of it against the actions of the Russian state. The authors performed an exhaustive review of official Russian strategy documents and statements from its leaders and policymakers and conducted interviews in Moscow. Using the information gathered, the authors outlined the broad contours of Russian grand strategy. They then chose six key elements of Russia's stated grand strategy for closer examination: the linkage between internal and external threats, the nature of Russia's role in its immediate neighborhood, concepts about the future of warfare, expeditionary requirements for Russia's military, Moscow's objectives vis-à-vis the West, and Russia's declared prioritization of engagement with non-Western powers. The authors tested each of these elements against empirical evidence about corresponding behaviors of the state. From this analysis, they suggest implications and considerations for U.S. policymakers, both in the U.S. Army and in the broader national security decisionmaking sphere
Title from PDF document (viewed July 30, 2021)
"Prepared for the United States Army.
"RAND Arroyo Center.
Keywords: Außenpolitik; Geopolitik; Sicherheitspolitik; Strategie; Russland; Geopolitics / Russia (Federation); Russia (Federation) / Foreign relations / Forecasting; Russia (Federation) / Foreign relations / History; Russia (Federation) / Politics and government / 21st century; Diplomatic relations; Geopolitics; Politics and government; Russia (Federation); 2000-2099; History